2017
DOI: 10.1111/pace.13231
|View full text |Cite
|
Sign up to set email alerts
|

The electromechanical substrate for response to cardiac resynchronization therapy in patients with right bundle branch block

Abstract: Patients with RBBB, left axis deviation, and no prior anterior MI may have LV dyssynchrony between the anterior and inferior walls that is correctable with CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Recently, several reports have suggested that RBBB patients with LBBB morphology in the limb leads have significant LV activation delays and respond better to cardiac resynchronization therapy (CRT) than those with typical RBBB. 7 , 8 Therefore, we believe that our patient was a candidate for CRT. However, due to physical limitations in activities of daily living secondary to a prior accident, the patient refused CRT.…”
Section: Case Reportmentioning
confidence: 84%
See 1 more Smart Citation
“…Recently, several reports have suggested that RBBB patients with LBBB morphology in the limb leads have significant LV activation delays and respond better to cardiac resynchronization therapy (CRT) than those with typical RBBB. 7 , 8 Therefore, we believe that our patient was a candidate for CRT. However, due to physical limitations in activities of daily living secondary to a prior accident, the patient refused CRT.…”
Section: Case Reportmentioning
confidence: 84%
“…During the evaluations of LS using speckle tracking echocardiography, an early systolic LV contraction was observed in the inferior wall, followed by late contraction in the anterior wall. 7 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…Several articles showed some correlation with electrical activation. [4][5][6][7] Still, the relationship between electrical disturbance and LVMD is partly unclear among these patients with RBBB.…”
Section: See Related Article Pp 621-630mentioning
confidence: 99%